PENGARUH ORIENTASI STRATEGIK, DAN STRUKTUR ORGANISASI TERHADAP INOVASI DAN KEUNGGULAN BERSAING PERUSAHAAN - Hendriyanto, Asepta (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2014)
The purpose of this research is to investigate and analyze the factors that affect thecompetitive advantage through product innovation, organization structure,strategy orientation. The method used is the method of survey data obtaineddirectly through questionnaires. Sampling using purposive random samplingmethods and methods of analysis used in this research was the path analysis.Based on the research results revealed that strategy orientation, and organizationstructure have effect on product innovation. And variable product innovation,have effect of the fircompetitive advantage.